Critical Thinking of Students with High and Low Mathematics Efficacy PISA Problem: A Case of Algebraic Task - Yanto, Arfan Dwi; Wijaya, Muhammad Avicenna Wahyu; Kohar, Ahmad Wachidul (Journal of Mathematical Pedagogy (JoMP), 2022)
This study aims to describe students' critical thinking on PISA problems on algebra content in terms of high and low mathematics efficacy. This descriptive qualitative research involves two junior high school students with high and low mathematics efficacy in one of the junior high schools in Jombang Regency. Data collection techniques were carried out by administering a mathematics efficacy questionnaire, Algebraic Content PISA Problems (ACPP), and interview guidelines. Data analysis was based on indicators of critical thinking ability (interpretation, analysis, evaluation, inference, explanation, and self-regulation). From the results of data analysis, critical thinking in the interpretation aspect shows that only students with high mathematics efficacy can write what is known and asked. Likewise, in the analysis aspect, it shows that only students with high mathematics efficacy can create a mathematical model of the given problem.  In the evaluation aspect, students with high and low mathematical efficacy can write complete problem-solving. Likewise, in the inference aspect, students with high and low mathematics efficacy were able to draw conclusions logically. Likewise, in the explanation aspect, students with high and low mathematical efficacy can write down the final results and provide reasons for the conclusions drawn. Meanwhile, in the aspect of self-regulation, students with high and low mathematics efficacy have conducted a review. Therefore, understanding students' critical thinking is very important for students and teachers to improve students' ability to solve PISA problems.